Good Corporate Governance Strategy and Firm Value: The Moderating Role of Firm Size - Taufik Hidayat; Rina Nurjanah; Oom Tikaromah; Fauzan Gilang Ramadhan (Politeknik Ganesha Medan, 2025)
This study analyses the effect of Good Corporate Governance (GCG) on firm value in the property and real estate sector in Indonesia, with firm size as a moderating variable. The phenomenon of fluctuating stock prices and decreasing company value in this sector is the background of the study. GCG is measured through the board of directors, board of commissioners, and audit committee, while firm value is calculated by Price Book Value (PBV). The research sample consisted of 24 property and real estate companies listed on the Indonesia Stock Exchange during the period 2013-2024, using a purposive sampling technique. The data was analysed using panel data regression with e-Views. The results indicate that the board of directors has a positive impact on firm value, whereas the boards of commissioners and the audit committee have no significant effect. Firm size weakens the effect of the board of directors on firm value, but does not moderate the effect of the board of commissioners and the audit committee. The findings indicate the complexity of the relationship between GCG, firm size, and firm value in the property and real estate sector in Indonesia. This research enriches agency and signaling theories, and shows that the role of the board of directors has a greater influence on smaller firms, suggesting that larger firms need to develop adaptive governance mechanisms to enhance the board’s effectiveness